A widened array of metrics (WAM) approach to characterize the urban acoustic environment; a case comparison of urban mixed-use and forest. (1st January 2022) - Lawrence, Bryce T.; Hornberg, Jonas; Haselhoff, Timo; Sutcliffe, Robynne; Ahmed, Salman; Moebus, Susanne; Gruehn, Dietwald
Highlights: Ecoacoustic indices and dB(A) compare contrasting 28-day urban mixed-use and forest cases. Data analysis includes mean hour-of-day, 7- and 28-day time series, and correlation plots. Results find BIO, NDSI, ACI indicate biophony in forests and M, AR, Ht anthrophony in mixed use. Multiple index 'indicator groups' can screen for biophony presence or absence. NDSI and BIO bias is reduced when sites analyzed separately, indicates biophony masking. Abstract: Sound pressure levels (SPL) in dB are the traditional noise measurement, but dB measures alone limit characterization of the complex urban acoustic environment. The aim of this paper is to apply alpha and beta ecoacoustic indices from soundscape ecology at two contrasting locations corresponding to an urban mixed-use corridor and a deciduous forest. Twenty acoustic indices and mean dB(A) are calculated from 2, 798 three-minute recordings taken every 26 min over a 28-day period. Acoustic indices are summarized by case with mean hour-of-day plots and 7- and 28-day time series plots to identify temporal patterns. Correlations to assess index relationships for each case separately and combined are presented. Acoustic indices provide complimentary information beyond SPL measures alone, especially in frequency and temporal domains, useful to identify patterns in the acoustic environment. Correlation between specific multiple indices at individual locations is a promising approach to identification of anthrophonic and biophonic dominated sonotopes.